THE INFLUENCE OF CHROMOPHORE PRESENCE IN AN EXPERIMENTAL BLEACHING GEL ON LASER ASSISTED TOOTH WHITENING EFFICIENCY - BORDEA, Ioana Roxana; LUCACIU, Patricia Ondine; CRIȘAN, Bogdan; MÎRZA, Camelia-Manuela; POPA, Daniela; MESAROȘ, Anca Ștefania; PELEKANOS, Stavros; CÂMPIAN, Radu Septimiu (Studia Universitatis Babeș-Bolyai Chemia, 2016)
The aim of this study was to assess the ability of chromophore to improve laser whitening procedures on bovine teeth. The teeth were previously stained with black tea. We evaluated the color change with the help of the Vita Easy Shade Spectrophotometer. Two batches of four teeth were prepared and immersed for 14 days in a solution of black tea. For the bleaching, an experimental gel was used. Batch I was kept in the gel without chromophore and batch II in the gel with chromophore. The teeth from both batches were kept for 30 sec in the gel and were afterwards irradiated with a diode laser (980nm). The statistical analysis showed significant differences between T1 (the measurement of the color after the staining process) and T2 (the measurement of color after the whitening process) for the first batch and T0 (the initial measurement of the color of the teeth) and T2 (the measurement of color after the whitening process) for the second batch.